2019
DOI: 10.1177/1741659019879888
|View full text |Cite
|
Sign up to set email alerts
|

A criminal mind? A damaged brain? Narratives of criminality and culpability in the celebrated case of Aaron Hernandez

Abstract: This article examines the media discourse surrounding the life and death of former National Football League player Aaron Hernandez, who died by suicide while incarcerated for first-degree murder. As a postmortem analysis found evidence of notable degenerative brain disease, differing explanations and speculations remain about the causes of his criminal behavior. This analysis illustrates how journalistic narratives attribute Hernandez’s criminality to either the material composition of his damaged brain or how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The whittleddown one-way message, where tau is the chief agent in the story, lays the groundwork for an overbearing focus on mechanical causes of violent tendencies as though they appear only after sport-induced brain trauma. In some alarming cases, violence committed by athletes outside of sport-assaults and murders, often of women-is being read as a symptom of CTE in the perpetrator (Henne and Ventresca 2019). This is neuro-reductionism par excellence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The whittleddown one-way message, where tau is the chief agent in the story, lays the groundwork for an overbearing focus on mechanical causes of violent tendencies as though they appear only after sport-induced brain trauma. In some alarming cases, violence committed by athletes outside of sport-assaults and murders, often of women-is being read as a symptom of CTE in the perpetrator (Henne and Ventresca 2019). This is neuro-reductionism par excellence.…”
Section: Discussionmentioning
confidence: 99%
“…With the agency of tau, a shift occurs wherein men who were violent as a job, and whose violence sometimes (often?) exceeds the field of play, become the victims of the drama (see also Henne and Ventresca 2019). Postmortem narratives are consolidated in some ways and not others, by the tellers, the journalists who selectively re-tell a story, and the scientists and doctors who speak on behalf of facts.…”
Section: Why Now? Agent Taumentioning
confidence: 99%
See 1 more Smart Citation
“…Grano further argues that the social values and conceptions of risk embedded within brain banking are unlikely to do justice to classed and raced aspects of risk-based decision making that are key to understanding the concussion crisis. Others (e.g., Brayton et al, 2019;Henne and Ventresca, 2019;Martin and McMillan, 2020) have likewise identified reductionist and/or neoliberal logics underpinning reporting into the concussion crisis; a conclusion that chimes with existing research suggesting that neuroscientific findings frequently perpetuate rather than challenge existing understandings of society (O'Connor et al, 2012;O'Connor and Joffe, 2013). These conclusions regarding the underpinning logics of concussion science and journalism are complementary to, and yet notably distinct from, those that consider overt conflicts of interest.…”
Section: Discussionmentioning
confidence: 80%
“…relation to contact sports and military personnel [36]. Mohammed Ali, possibly the greatest heavyweight boxer of all times was believed to suffer from Dementia Pugilistica, and it is thought that he died of its complications in June 2016 [37][38]. Aaron Hernandez, a former NFL (National Football League) player and a convicted murderer was sentenced to life in prison without the possibility of parole.…”
Section: Open Access Journal Of Gerontology and Geriatric Medicinementioning
confidence: 99%